PHYTOREMEDIATION OF TEXTILE WASTEWATER USING AQUATIC FREE-FLOATING PLANT: A SUSTAINABLE APPROACH FOR WATER TREATMENT - Saumya Gupta1, Khushbu Verma2* (Chelonian Research Foundation, 2023)
The study aims to summarize the phytoremediation potential of Limnobium spongia and its effectiveness in the removal of heavy metals and phosphorus from wastewater. The plants were kept in the Bagru industrial textile wastewater and Sanganer industrial textile wastewater for the observation of metal and phosphorus extraction for 28 days. The plants were collected after 28 days and determined for Heavy metal and phosphorus analysis with the help of an Atomic Absorption Spectrophotometer. The result shows that Limnobium spongia accumulates heavy metals and phosphorus from Bagru and Sanganer industrial wastewater but with time plant growth also deteriorates because of the physiochemical and heavy metal toxicity of wastewater. In conclusion, This information aids in understanding that Limnobium spongia presents a valuable approach for heavy metal analysis and assessment of environmental pollution. Keywords:- Phytoremediation, Contamination, Industrial wastewater, Heavy metals, Atomic Absorption Spectrophotometer (AAS).